Heart rate changes after manual techniques on cervical spine: Systematic review: Cervical manual techniques on heart rate - Zago, Julio; Drummond, Adriano; Amatuzzi, Fellipe; Rondinel, Tatiana; Queiroz, Rogério; Nascimento, Leonardo; Pivetta, Renan; Chiappa, Gaspar (Manual Therapy, Posturology & Rehabilitation Journal, 2025)
Background: The autonomic nervous system (ANS) can be modulated through various manual therapy techniques (MTT) on the cervical spine. However, it remains unclear whether these modulations have clinically relevant effects on the heart rate (HR) of individuals with craniocervical dysfunctions (CCD). Objective: This study aims to review existing research on MTT applied to the cervical spine and its effects on HR in patients with CCD. Methods: This study was registered with the International Prospective Register of Systematic Reviews (PROSPERO), registration number CRD42019126739. No funding was received for this study. Articles were identified through searches in PubMed, Web of Science, CENTRAL and EMBASE. Eligible studies assessed HR before and after MTT. The risk of bias was evaluated using the Physiotherapy Evidence Database (PEDro) scale, and the certainty of the evidence was determined using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) approach. Results: Three articles met the eligibility criteria. One study reported a significant increase in HR following the application of the high-velocity low-amplitude (HVLA) technique, while another indicated clinically significant increase in HR after mobilization techniques. Both studies demonstrated high methodological quality but were classified as having a very low level of evidence. Discussion: The findings suggest that MTT can stimulate the ANS, whether through HVLA or mobilization techniques, regardless of the specific cervical level targeted. However, the inconsistency of the data across studies complicates more precise analyses.